Teaching Speaking Eighth Grade Students of Junior High School through Drama Technique - Yulia Utami; Andrian Nuriza Johan (Scripta : English Department Journal, 2020)
The aim of this study is to find out whether the use of drama is effective or not in teachingspeaking at the eighth grade of State Junior High School (SMPN) 1 Pejagoan in the academic year of2017/2018. In this study , the two classes of the eighth grade were taken as the population and sample ofSMP N 1 Pejagoan in the academic year of 2017/2018. There were 60 students taken as the samples .The data analysis techniques employed were descriptive and inferential analysis. The formula of t-testwas applied to prove whether it is effective or not. After analyzed the data, the researcher found that thestudents’ achievement of experiment group was better than control group. The means score ofexperimental group was 85.60 and the means score of control group was 73.73, it could be seen from thefinal result of t-test analysis which stated that t-value was higher than t-table (7.54>2.00). Therefore, itcan be conclude that the use of Drama Technique in teaching speaking at the eighth grade of SMP N 1Pejagoan in the academic year of 2017/2018 is effective.